Single‐Atom Catalysts: Emerging Multifunctional Materials in Heterogeneous Catalysis - Zhang, Huabin; Liu, Guigao; Shi, Li; Ye, Jinhua (Advanced energy materials, 2018)
Supported metal nanoparticles are the most widely investigated heterogeneous catalysts in catalysis community. The size of metal nanostructures is an important parameter in influencing the activity of constructed catalysts. Especially, as coordination unsaturated metal atoms always work as the catalytically active centers, decreasing the particle size of the catalyst can greatly boost the specific activity per metal atom. Single‐atom catalysts (SACs), containing single metal atoms anchored on supports, represent the utmost utilization of metallic catalysts and thus maximize the usage efficiency of metal atom. However, with the decreasing of particle size, the surface free energy increases obviously, and tends to aggregate into clusters or particles. Selection of an appropriate support is necessary to interact with isolated atoms strongly, and thus prevents the movement and aggregation of isolated atoms, creating stable, finely dispersed active sites. Furthermore, with uniform single‐atom dispersion and well‐defined configuration, SACs afford great space for optimizing high selectivity and activity. In this review, a detailed discussion of preparing, characterizing, and catalytically testing within this family is provided, including the theoretical understanding of key aspects of SACs materials. The main advantages of SACs as catalysts and the challenges faced for further improving catalytic performance are also highlighted. In this review, a detailed discussion of preparing, characterizing, and catalytically testing within this family is provided, including the theoretical understanding of key aspects of single atom catalysts (SACs) materials. The main advantages of SACs as catalysts and the challenges faced for further improving catalytic performance are also highlighted.